ASSESSMENT OF THE IMPACT OF FAMILY BUSINESS ON POVERTY REDUCTION (Marketing Journal, 2025)
This article provides a scientific analysis of the key factors influencing the development of family entrepreneurship and its impact on poverty reduction. The study evaluates the effects of financial support, labor resources, social capital, and infrastruc ture on household income levels. Econometric forecasting results indicate that expanding family entrepreneurship can reduce poverty by approximately 1.5 –2.3 percentage points annually. The findings highlight family entrepreneurship as an effective mechanis m for enhancing economic resilience and improving social welfare.
Keywords: family entrepreneurship; poverty reduction; economic activity; household income; forecasting; regression analysis; social capital; employment. № 1 203